Temporal Trends and Outcomes of Percutaneous and Surgical Aortic Valve Replacement in Patients With Atrial Fibrillation - Wu, Jing; Li, Chenguang; Zheng, Yang; Tong, Qian; Liu, Quan; Cong, Xiaoqiang; Lou, Zhiyang; Zhang, Mingyou (Frontiers in Cardiovascular Medicine, 2020)
Objectives: The aim of this study was to evaluate the temporal trends of transcatheter aortic valve replacement (TAVR) in severe aortic stenosis (AS) patients with atrial fibrillation (AF) and to compare the in-hospital outcomes between TAVR and surgical aortic valve replacement (SAVR) in patients with AF. Background: Data comparing TAVR to SAVR in severe AS patients with AF are lacking. Methods: National inpatient sample database in the United States from 2012 to 2016 were queried to identify hospitalizations for severe aortic stenosis patients with AF who underwent isolated aortic valve replacement. A propensity score-matched analysis was used to compare in-hospital outcomes for TAVR vs. SAVR for AS patients with AF. Results: The analysis included 278,455 hospitalizations, of which 124,910 (44.9%) were comorbid with AF. Before matching, TAVR had higher in-hospital mortality than SAVR (3.1 vs. 2.2%, p < 0.001); however, there was a declining trend during the study period (Ptrend < 0.001). After matching, TAVR and SAVR had similar in-hospital mortality (2.9 vs. 2.9%, p < 0.001) and stroke. TAVR was associated with lower rates of acute kidney injury, new dialysis, cardiac complications, acquired pneumonia, sepsis, mechanical ventilation, tracheostomy, non-routine discharge, and shorter length of stay; however, TAVR was associated with more pacemaker implantation and higher cost. Of the patients receiving TAVR, the presence of AF was associated with an increased rate of complications and increased medical resource usage compared to those without AF. Conclusions: In-hospital mortality and stroke for TAVR and SAVR in AF, AS are similar; however, the in-hospital mortality in TAVR AF is declining and associated with more favorable in-hospital outcomes.